Оценка эффективности гидропаровой турбины для утилизации избыточного тепла шахтного энергокомплекса - Кирсанов, М.В.; Лукиша, А.П. (Геотехническая механика, 2012)
Отримано співвідношення для калькуляції тягового реактивного момента та коефіцієнгту корисної дії (ККД) установки з реактивною гідропаровою турбіною (РГПТ) в залежності від чотирьох суттєвих параметрів її роботи. Зроблено аналіз цих співвідношень. Для типових параметрів роботи РГПТ значення термічного ККД досягає 46% від максимально можливого за циклом Карно. Тому зроблено висновок про доцільність використання технології РГПТ в складі шахтного енергокомлекса. Relationships for calculation of moving jet torque and efficiency factor of jet hydro – vapour turbin’s (JHVT) unit in depending on four substantial parameters of its work was derived. The analysis of these relationships is done. For the typical parameters of work of the JHVT value of thermal efficiency factor amount 46% from maximally possible by Carnot’s cycle. A conclusion is therefore done about expedience of the use of the JHVT-technology in composition of mine’s energocomplex.